Do gold nanoparticles consistently benefit crop plants under both non-stressed and abiotic stress conditions? - Alabdallah Nadiyah M. (Nanotechnology Reviews)
Gold nanoparticles (AuNPs) have become a valuable tool for enhancing crop production under both non-stressed and abiotic stress conditions. However, the mechanisms by which AuNPs enter plant leaves and boost growth and yield are not fully understood. Abiotic stresses negatively impact plant growth and yield by affecting morphological, physiological, and metabolic processes, such as nutrient and water uptake, photosynthetic systems, and antioxidant activities. AuNPs help protect membranes, maintain water balance, and improve nutrient and water absorption, and they scavenge reactive oxygen species, which significantly increase plant growth under stress conditions. This review explored the biological synthesis of AuNPs, their entry mechanisms into leaves, and their positive impacts on plants under both normal and stressful conditions. It also highlighted several research gaps in the field of AuNP-mediated abiotic stress tolerance. This comprehensive review serves as an excellent resource for future researchers interested in using AuNPs as an eco-friendly approach to enhance abiotic stress tolerance in plants.